2016
DOI: 10.1111/cen.13049
|View full text |Cite
|
Sign up to set email alerts
|

Effects of testosterone replacement on metabolic and inflammatory markers in men with opioid‐induced androgen deficiency

Abstract: In this 14-week trial, testosterone administration in men with opioid-induced androgen deficiency was not associated with worsening of metabolic and inflammatory markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 36 publications
(91 reference statements)
0
6
0
Order By: Relevance
“…A Fountas and others Effects of opioids on endocrine system www.eje-online.org occurred in neither group. Notably, Huang et al, in a placebo-controlled, double-blind randomized trial from the same centre of 64 non-diabetic men (aged between 18 and 64 years) on opioid analgesics for chronic noncancer pain and morning total testosterone <12 nmol/L (as measured by liquid chromatography-tandem mass spectrometry), randomised to 14 weeks of transdermal testosterone gel or placebo gel daily, found that changes in lipid profile, fasting glucose and insulin, homeostatic model assessment for insulin resistance and C-reactive protein were similar from baseline to the end of treatment in both groups; glucose and insulin response to 75 g oral glucose load, inflammatory markers and adipokines also did not differ between the two groups (42). However, the duration of this study was not long enough to evaluate cardiovascular safety of testosterone therapy in these patients.…”
Section: :4 R187 Reviewmentioning
confidence: 98%
“…A Fountas and others Effects of opioids on endocrine system www.eje-online.org occurred in neither group. Notably, Huang et al, in a placebo-controlled, double-blind randomized trial from the same centre of 64 non-diabetic men (aged between 18 and 64 years) on opioid analgesics for chronic noncancer pain and morning total testosterone <12 nmol/L (as measured by liquid chromatography-tandem mass spectrometry), randomised to 14 weeks of transdermal testosterone gel or placebo gel daily, found that changes in lipid profile, fasting glucose and insulin, homeostatic model assessment for insulin resistance and C-reactive protein were similar from baseline to the end of treatment in both groups; glucose and insulin response to 75 g oral glucose load, inflammatory markers and adipokines also did not differ between the two groups (42). However, the duration of this study was not long enough to evaluate cardiovascular safety of testosterone therapy in these patients.…”
Section: :4 R187 Reviewmentioning
confidence: 98%
“…In this issue of the journal, Huang and colleagues report secondary analyses of this same trial, but limited to 64 men without diabetes mellitus. 11 Testosterone (n = 36), compared with placebo (n = 28), had no effect on fasting cholesterol (total, HDL and LDL), triglycerides, glucose, insulin, insulin resistance (HOMA), HbA1c, leptin, adiponectin and CRP, as well as glucose and insulin measured one and two hours after a standard 75 g oral glucose tolerance test. In these secondary analyses, smaller changes in lipids that would be relevant over a longer period of exposure were not excluded as the sample size only permitted large effects (exceeding standardized mean differences of 0Á7) to be detected.…”
mentioning
confidence: 95%
“…Strong opioids are not recommended by the German and EULAR guidelines, discouraged by the Canadian guidelines and only considered if other medicinal and nonmedicinal therapies have been exhausted in the APS guidelines. They are often poorly effective for the pain and there are significant potential long-term adverse effects including increased risk of mortality, 116,117 reduction of testosterone 118 and opiate-induced hyperalgesia. 119 The WHO pain ladder was designed for cancer pain, and not intended for use in chronic pain.…”
Section: Pharmacologicmentioning
confidence: 99%